Enhancing Students’ Classroom Participation: Can the Talking Chips Technique Improve the Speaking Skills of Eighth-Grade Students at SMPN 2 Ubud? - Ni Putu Diah Yudiastari; Ni Wayan Krismayani; Luh Ketut Sri Widhiasih (Journal on Studies in English Language Teaching (JOSELT), 2026)
This study was prompted by the low English-language proficiency of eighth-grade students at SMPN 2 Ubud, characterized by issues with pronunciation, fluency, and comprehension in speaking. One learning method to deal with this problem is the Talking Chips. The purpose of this study is to improve the speaking skills of eighth-grade students at SMPN 2 Ubud during the academic year 2025–2026 using Talking Chips. Classroom Action Research is a study methodology that consists of two cycles: planning, action, observation, and reflection (CAR). The research subjects were thirty-three students from class VIII-D. The research tools included a questionnaire to measure student responses and a speaking exam (pre- and post-test). The study found that the children’s speaking skills increased dramatically. In cycles I and II, the average student score rose from 44.24 on the pre-test to 64.66 on the post-test and 79.54 on the post-test, respectively. Additionally, the survey results showed that the students received the Talking Chips method well. The results show that using the Talking Chips can improve students’ speaking skills. English teachers are encouraged to adopt the Talking Chips strategy as an alternative teaching method to improve students’ speaking skills and engagement.